Inhibiting WNT and NOTCH in renal cancer stem cells and the implications for human patients - Annika Fendler (Nature Portfolio, 2020)
Cancer stem cells are thought to be largely resistant to treatment and can be responsible for tumour recurrence. Here, using renal cancer organoids, self-renewing sphere cultures and PDX from patients, the authors show that the proliferation of stem cells within organoids, PDX and spheres can be blocked by the concomitant inhibition of the NOTCH and WNT pathways.